Evaluation of Chemical Chaperones on the Transient Expression in Chinese Hamster - Azam Rahimpour (Journal of Global Pharma Technology, 2017)
Recombinant proteins play an important role in biomedical and basic science researches. In this regard, mammalian cells have widely use in monoclonal antibodies. Improper aggregation complex recombinant proteins have been known as a bottleneck in successful production of active bio-therapeutics. Anti-CD52 is efficient immunosuppressive agents of therapeutic applications especially in autoimmune diseases. In this study, effects of four chemical Chaperones including DMSO and 4-phenyl butyrate (4-PBA) on transient of a recombinant evaluated during six days. Analysis of the expression level showed up to 2 fold in DMSO treated cells, while 4-PBA treatment improved antibody expression up to 50%, 30% and 10%, respectively. Keywords: Monoclonal antibody, Transient expression, Chemical chaperone.